Soft drink consumption and liver fibrosis in type 2 diabetes - Ferro, Arianna; Bollati, Martina; Caviglia, Gian Paolo; Armandi, Angelo; Bellini, Stefania; Limoncelli, Selene; Mengozzi, Giulio; Barutta, Federica; Broglio, Fabio; Beccuti, Guglielmo; Bugianesi, Elisabetta; Durazzo, Marilena; et al. (Frontiers in Nutrition, 2025)
IntroductionMetabolic dysfunction–associated steatotic liver disease (MASLD) is highly prevalent among individuals with type 2 diabetes mellitus (T2DM), and liver fibrosis represents its strongest predictor of adverse outcomes. Soft drinks (SDs), a major source of added sugars and fructose, have been linked to metabolic disorders, but evidence on their relationship with liver fibrosis in patients with T2DM is limited. This study investigated the association between SDs consumption and liver fibrosis in adults with both T2DM and liver steatosis.MethodsWe analyzed 273 participants from the TESEO-DM cohort with imaging-documented hepatic steatosis (Controlled Attenuation Parameter, CAP ≥248 dB/m). SDs intake was assessed using the validated EPIC food frequency questionnaire and categorized as rarely/never, 1–4 servings per month, or >1 servings per week. Liver stiffness measurement (LSM) was assessed using vibration-controlled transient elastography and LSM >7 used as cut-off to define significant liver fibrosis.ResultsIn age- and sex-adjusted linear regression, SDs intake was directly associated with LSM (β = 0.181, 95% CI: 0.062–0.299, p = 0.003). The association remained significant after adjustment for diabetes duration, total caloric intake, high-density lipoprotein cholesterol, and either body mass index (β = 0.153, 95% CI: 0.032–0.274, p = 0.014) or CAP (β = 0.150; 95% CI: 0.028–0.274; p = 0.017). In logistic regression, participants consuming >1 SDs per week had increased odds of significant liver fibrosis (OR: 3.77, 95% CI: 1.33–10.66) compared with those rarely or never consuming SDs independent of age, sex, diabetes duration, and obesity. Inclusion into the model of tertiles of CAP in place of obesity did not modify the results (OR: 3.11 95% CI: 1.09–8.86).ConclusionsThese findings suggest that even modest soft drink consumption is independently associated with higher liver stiffness in individuals with T2DM and liver steatosis, supporting recommendations to limit added sugar intake for liver health.